Isolasi, Pemurnian dan Karakterisasi Parsial Soybean Stunt Virus - Sri Sulandari; Y. B. Sumardiyono; Roechan Roechan (Jurnal Perlindungan Tanaman Indonesia, 1997)
The objective of this study was isolation and characterization of Soybean Stunt Virus, the causal agent of soybean stunt disease. The virus was isolated with single lesion method through Chenopodium amaranticolor and Vigna unguiculata, and then propagated on Nicotiana tabacum var. Xanthi. Differential centrifugation method was used for purification. Virus isolate obtained from Bogor was used for futher studies. The result showed that SSV could be isolated on C. amaranticolor, but not on V. unguiculata and then propagated on Niconana tabacum var. Xanthi without any symptom. Purified virus showed A260/A280 = 1.55, lower than that of CMV. The virion were small isometric particles, about 30 nm in diameter. Coat protein consists of a single type of subunit protein, with molecular weight about 29 kD.